Ginseng improves cognitive deficit via the RAGE/NF-κB pathway in advanced glycation end product-induced rats - Tan, Xiaobin (J Ginseng Res, 2015)
BACKGROUND: Ginseng, the root of Panax ginseng (PG), is used widely as a herbal medicine to prevent and treat various diseases. Panax ginseng has pharmacological effects on neurodegenerative diseases such as Alzheimer's disease (AD). The present study evaluated the neuroprotective effects of PG and its possible neuroprotective mechanisms in advanced glycation end product (AGE)-induced AD in a rat model. METHODS: Advanced glycation end products were injected bilaterally into the CA3 region of the rats' brains. The Morris water maze test and step-down type passive avoidance test were performed to evaluate their memory and cognitive abilities. The oxidation indexes in the hippocampus were detected. Immunohistochemistry was conducted to visualize the receptors for advanced glycation end products (RAGEs) and nuclear factor-kappa-light-chain-enhancer of activated B cell (NF-κB). RESULTS: Behavioral results showed that PG (1 g/kg, 0.5 g/kg, and 0.25 g/kg) significantly shortened the escape latency, remarkably increased the number of crossing times, significantly decreased the number of errors, and prolonged the latency in rats with AGE-induced AD. Panax ginseng also significantly reduced the malondialdehyde level, increased the glutathione content, and increased superoxide dismutase activity in the hippocampus. Panax ginseng significantly decreased the expression of RAGE and NF-κB. The blockade of anti-RAGE antibody could significantly reduce AGE-induced impairments and regulate these expressions. CONCLUSION: Our results demonstrated that PG significantly inhibits AGE-induced memory impairment and attenuates Alzheimer-like pathophysiological changes. These neuroprotective effects of PG may be associated with the RAGE/NF-κB pathway. Our results provided the experimental basis for applying PG in preventing and treating AD.